2008
DOI: 10.1055/s-0028-1085095
|View full text |Cite
|
Sign up to set email alerts
|

Intrahepatic Portal Venopathy and Related Disorders of the Liver

Abstract: Intrahepatic portal venopathy leads to various entities that are important causes of portal hypertension. Noncirrhotic portal fibrosis (NCPF) occurs in the Indian subcontinent, whereas idiopathic portal hypertension (IPH) occurs in Japan although the pathogenesis and presentation of both are similar. NCPF presents mainly with upper gastrointestinal bleeding; IPH presents with massive splenomegaly. The liver functions are preserved. Wedged hepatic venous pressure is normal, but portal venous pressure is high in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 77 publications
1
29
0
2
Order By: Relevance
“…Finally, a total of 69 well-characterized patients with IPH were included. Mean duration of follow-up from diagnosis was 6.7 6 4.6 years (median, 6; range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, a total of 69 well-characterized patients with IPH were included. Mean duration of follow-up from diagnosis was 6.7 6 4.6 years (median, 6; range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Resultsmentioning
confidence: 99%
“…In those with symptoms, confirming previous observations, VB was the most common initial manifestation. 1,5,13 The lack of specific symptoms or laboratory abnormalities may defer the diagnosis of IPH. Indeed, 7% of our patients were previously misdiagnosed with cryptogenic cirrhosis and the diagnosis was delayed for more than 1 year in 25%, confirming that IPH diagnosis is demanding and requires a high index of suspicion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 EPIDEMIOLOGY NCIPH has been reported from all parts of the world, though more so from developing countries where it is most commonly encountered in young males in their third to fourth decade. [16][17][18] In contrast, in Japan and the West there is a female preponderance and a tendency to present around the fifth decade. 19 The relative rarity of the disease in the West and an apparent decline in its incidence elsewhere as living standards and hygienic conditions improve support the notion that enteropathy plays a role in disease pathogenesis.…”
Section: Definitionmentioning
confidence: 99%
“…1 NRH can also be considered a component of intrahepatic portal venopathy, an entity which also includes diseases like noncirrhotic portal fibrosis (NCPF) in the Indian subcontinent and idiopathic portal hypertension (IPH) in Japan. 2 Overall, NRH is an uncommon condition with only a few hundred cases described in the world literature. Autopsy studies have shown NRH in 2.6% of autopsy livers with a higher prevalence (5.6%) in patients aged more than 80 years, and those having systemic arteritis, polymyalgia rheumatica and massive tumor infiltration of liver.…”
mentioning
confidence: 99%